Antioxidant and antibacterial activities of Butea monosperma (Lam.) Taub. flower extracts - Khamsuk, Kumpanat; Onongarj, Parichat; Phaiboon, Nalita; Chaisawang, Pornthip; Pounsan, Sutida (Health Science Journal of Thailand, 2025)
Butea monosperma (Lam.) (commonly known as the flame of the forest or Palash) is a plant that has been used in traditional medicine for a long time. It has been reported to contain various bioactive compounds such as flavonoids, phenolics, and tannins, which possess antioxidant properties. These compounds help neutralize free radicals and reduce oxidative stress, making the plant a subject of interest for its potential health benefits and therapeutic applications. In the present study, total phenolic compounds, antioxidant activities, and antibacterial activities of the hydroethanolic extract from the flower of B. monosperma were evaluated. The total phenolic compound was quantified based on the Folin–Ciocalteu method, and the antioxidant activities of the extracts were assessed through the 1,1-diphenyl-2-picryl-hydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. The broth dilution method, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) were used to evaluate the antibacterial activity of the extracts against Staphylococcus aureus, Streptococcus mutans, Bacillus subtilis and, Escherichia coli. The results revealed that the total phenolic content of the extracts was 65±0.014 mg of gallic acid equivalent/g of extract. Additionally, the antioxidant activities in terms of IC50 value of the extracts were 0.44±1.181 mg/ml and 16.054±0.188 mg/ml, according to the DPPH and the FRAP assay. Crude extracts of B. monosperma flower also demonstrated antibacterial activity against selected bacterial strains, with MIC and MBC values ranging from 1.56 to 200 mg/mL. In summary, the results suggest that flower extracts of B. monosperma may serve as valuable sources of bioactive compounds with antioxidant and antibacterial properties. However, further research involving the isolation and purification of these bioactive compounds is necessary to elucidate their mechanism of action.